Diet and gut microbiota of two supralittoral amphipods Orchestia montagui and Talitrus saltator living in different microhabitats. (15th October 2017) - Abdelrhman, Khaled F.A.; Bacci, Giovanni; Nistri, Annamaria; Mengoni, Alessio; Ugolini, Alberto
Abstract: Talitrus saltator (Montagu) and Orchestia montagui Audouin live in different microhabitats of the same supralittoral belt. T. saltator can be found in the damp sand of beaches with scarce or absent wracked material near the water line. O. montagui is frequently found in the Posidonia banquettes or under wracked material, often in contact with the substrate. This study investigates the effect of diet on species-specific gut microbiota patterns in these talitrid species. Adults were collected and fed with artificial food (commercial fish food and pieces of blotting paper) for 51 days. Gut microbiota were analyzed at five time intervals (0 h, 24 h, 7, 23 and 51 days) by 16S rRNA gene metagenomic analysis and by estimating the relative abundance of cellulases (glycosyl hydrolase gene family 48, GHF48) gene copies. The gut microbiota of O. montagui was more affected than that of T. saltator by diet shift. Although the taxonomic profile of the gut microbiota varied with time in both species, with an increase of Protobacteria in O. montagui and of Actinobacteria and Bacteroidetes in T. saltator, genes involved in cellulose degradation (GHF48 family) showed a large-scale increase in O. montagui but not in T. saltator. We conclude that the diet variation has different influence on the composition of gut microbiota in the two talitrid species in accordance with their different alimentary habits: the more generalist T. saltator (detritivore, grazer, and scavenger) showed less changes in its gut microbiota composition than the more specialist O. montagui (detritivore and grazer), which strongly modified its gut microbiota composition by the captivity diet. Highlights: Talitrus saltator and Orchestia montagui are two littoral amphipods with contrasting foraging behavior. Here we investigate the resilience of the gut microbiota in these two species under controlled laboratory conditions. Results showed the gut microbiota of O. montagui being more affected as expected from a more diet specialized species.